Middle level social studies education in Turkey: A window to citizenship education - (:unkn) unknown (Taylor and Francis, 2019)
The author traces the historical development of social studies and citizenship education programs in Turkey today, with a focus on which types of information, skills, and values are being taught to middle grades students. The chapter concludes with a discussion of teacher training and explains briefly its historical development process and the current teacher training system. © 2020 Taylor & Francis. All rights reserved.